PERAN GAYA KEPEMIMPINAN DALAM MEMEDIASI KECERDASAN EMOSIONAL TERHADAP KEPUASAN KERJA PEGAWAI PADA BADAN PUSAT STATISTIK PROVINSI SULAWESI TENGGARA - Umar Wirahadi Kusuma; Nurwati Nurwati; La Ode Kalimin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The purpose of this study was to examine and explain the leadership style in mediating role of emotional intelligence on job satisfaction of employees at the Central Bureau of Statistics of Southeast Sulawesi province. The approach of this research is a survey method with a reseach expalanatory reseach. Collecting data in the research done by using the instrument in the form of a questionnaire. The population of this study were employees of the Central Statistics Agency southeast Sulawesi province 50 people while the sampling technique used is accidential sampling. Analytical equipment used to test the hypothesis is Partial Least squer (PLS). The results showed that the style of leadership and a significant positive effect on emotional intelligence and employee satisfaction, Then the emotional intelligence and significant positive effect on employee satisfaction and leadership style. Finally, this research can prove that the leadership style acts as a partial mediation (partial mediation) effect between intelligence emosionl and employee satisfaction. That is significantly influenced by the style of leadership in emotional intelligence and leadership style influence employee satisfaction and emotional intelligence significantly influence employee satisfaction.Keywords: leadership style, emotional intelligence, and job satisfaction